A Mixed‐Methods Examination of Counselors' Social Class and Socioeconomic Status Perceptions. Issue 2 (30th June 2021) - Cook, Jennifer M.; Ong, Lee Za; Zavgorodnya, Olga
Abstract : We investigated how counselors ( N = 157) perceived social class and socioeconomic status (SES) via a mixed‐methods design. Among other findings, the results revealed participants provided limited or SES‐only responses when they defined social class. We describe counseling practice and training implications from a culturally informed, humanistic perspective.